2017
DOI: 10.1182/blood-2017-04-780205
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-type plasminogen activator regulates macrophage activation and innate immunity

Abstract: Tissue-type plasminogen activator (tPA) is the major intravascular activator of fibrinolysis and a ligand for receptors involved in cell signaling. In cultured macrophages, tPA inhibits the response to lipopolysaccharide (LPS) by a pathway that apparently requires low-density lipoprotein receptor-related protein-1 (LRP1). Herein, we show that the mechanism by which tPA neutralizes LPS involves rapid reversal of IκBα phosphorylation. tPA independently induced transient IκBα phosphorylation and extracellular sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
117
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(127 citation statements)
references
References 68 publications
8
117
2
Order By: Relevance
“…In the absence of plasminogen, EI‐tPA (12 nM) reversed the effects of LPS (0.1 μg/mL) on expression of TNF‐α, IL‐1β, IL‐6, and CCL2 (Fig. B), confirming our earlier results . EI‐tPA also reversed the effects of LPS on expression of IL‐10 and IL‐1ra (Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In the absence of plasminogen, EI‐tPA (12 nM) reversed the effects of LPS (0.1 μg/mL) on expression of TNF‐α, IL‐1β, IL‐6, and CCL2 (Fig. B), confirming our earlier results . EI‐tPA also reversed the effects of LPS on expression of IL‐10 and IL‐1ra (Fig.…”
Section: Resultssupporting
confidence: 88%
“…We previously demonstrated that BMDMs express the NMDA‐R, which serves as an essential receptor in the pathway by which tPA suppresses cytokine expression by BMDMs in response to LPS . We therefore tested whether the NMDA‐R is involved in the proinflammatory response to plasmin by treating BMDMs with the noncompetitive NMDA‐R antagonist, Dizocilpine/MK‐801 (1.0 μM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No unexpected toxicities were detected in the brentuximab vedotin plus AVD arm; only 2 of the patients relapsed, and both have since achieved second remission. 1 Although these phase 1/2 data are limited by the small number of patients (n 5 51), they have spurred significant interest in brentuximab vedotin plus AVD as front-line therapy for advanced Hodgkin lymphoma. Because of the potential of enhanced efficacy and the elimination of bleomycin-induced pulmonary toxicity, could brentuximab vedotin replace bleomycin in ABVD as the standard of care for these patients?…”
mentioning
confidence: 99%